Regional seepage and slope stability analyses with historical rainfall analysis - Long, Yilin (Nanyang Technological University, 2023)
Climate change is projected to cause more intense and unpredicted rainfalls in the future, which might also result in more rainfall-induced slope failures in Singapore. In Singapore, residual soil slopes often experience rainfall-induced failures within the unsaturated zone due to the deep groundwater tables. As a result, it is crucial to consider unsaturated soil mechanics when conducting slope stability analyses to identify critical slope areas accurately. Conducting rainfall analyses is important in understanding the patterns and predicting future rainfall events. However, it is also crucial to ensure the accuracy of the results. Hence, this project compared the Root Mean Square Error (RMSE) of two methods and found that the proposed method generally had lower RMSE values than the past research method, except in some years. The rainfall distribution maps were produced using ArcMap using the maximum daily and maximum 5-day antecedent rainfall results from kriging interpolation. It was observed that the spatial distribution for the daily and 5-day antecedent rainfall did not always coincide. The distribution maps were then utilised to obtain the rainfall intensity for GEOtop analyses, which included the maximum daily and maximum 5-day antecedent rainfalls, as well as the zone of interest. Thereafter, Scoops3D was used to assess the slope stability under the two different rainfall events. Two soil slopes within a zone of Bukit Timah Granite in Singapore were selected for slope stability assessment due to the relatively higher rainfall intensity on these 2 slopes based on the rainfall analyses conducted in this study. Due to the high permeability of the soil, further study of the Scoops3D results revealed that these slopes are more likely to experience slope failures when subjected to high intensity but short duration rainfall as compared to prolonged and low intensity rainfall.